Significance of the Wnt signaling pathway in coronary artery atherosclerosis - Khan, Kashif; Yu, Bin; Tardif, Jean-Claude; Rhéaume, Eric; Al-Kindi, Hamood; Filimon, Sabin; Pop, Cristina; Genest, Jacques; Cecere, Renzo; Schwertani, Adel (Frontiers in Cardiovascular Medicine, 2024)
The progression of coronary atherosclerosis is an active and regulated process.The Wnt signaling pathway is thought to play an active role in the pathogenesis of several cardiovascular diseases, however a better understanding of this system in atherosclerosis is yet to be unravelled.-Real time quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) and Western blotting were used to quantify the expression of Wnt3a, Wnt5a and Wnt5b in human coronary plaque, and immunohistochemistry was used to identify sites of local expression. To determine the pathologic significance of increased Wnt, we treated human vascular smooth muscle cells (vSMCs) with Wnt3a, Wnt5a, and Wnt5b recombinant proteins and assessed for changes in cell differentiation and function. Results -RT-PCR and Western blotting showed a significant increase in the expression of Wnt3a, Wnt5a, Wnt5b and their receptors in diseased compared to non-diseased coronary arteries. Immunohistochemistry revealed abundant expression of Wnt3a and Wnt5b in diseased compared to little signal in normal coronary arteries. Immunostaining of Wnt3a and Wnt5b was found largely in inflammatory cells and myointimal cells. Treatment of vSMCs with Wnt3a, Wnt5a, and Wnt5b resulted in increased vSMCs differentiation, migration, calcification, oxidative stress, and impaired cholesterol handling. Conclusions -This study demonstrates upregulation of 3 important members of the canonical and noncanonical Wnt signaling pathways and their receptors in coronary atherosclerosis, and shows an important role for these molecules in plaque development through increased cellular remodelling and impaired cholesterol handling.